2014
DOI: 10.1111/jfbc.12088
|View full text |Cite
|
Sign up to set email alerts
|

Flavonols from the Ripe Fruits ofOpuntia ficus-indicaVar.sabotenProtect Neuronal PC-12 Cells against Oxidative Stress

Abstract: Fruits of prickly pear cactus Opuntia ficus-indica have been traditionally used as a folk medicine with various pharmacological activities, partly due to their antioxidative flavonoids. The ripe fruits of O. ficus-indica var. saboten were extracted with 70% v/v aqueous ethanol to obtain phenolic extracts, which were separated into five fractions of n-hexane, chloroform, ethyl acetate, n-butanol and water. The ethyl acetate fraction showed the highest levels of total phenolics, total flavonoids and antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…PC-12 neuronal cell line viability increased up to 73%, after H 2 O 2 insult, at 100 µg/mL of ethyl acetate extract of Korean “Saboten” fruits [ 136 ]. Portuguese wild fruits juice extracts showed an anti-proliferative effect on the human colon cancer cell line HT29, an effect that may be attributed to an increment of 12 to 16% of ROS compared to the control [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…PC-12 neuronal cell line viability increased up to 73%, after H 2 O 2 insult, at 100 µg/mL of ethyl acetate extract of Korean “Saboten” fruits [ 136 ]. Portuguese wild fruits juice extracts showed an anti-proliferative effect on the human colon cancer cell line HT29, an effect that may be attributed to an increment of 12 to 16% of ROS compared to the control [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant capacities as determined by ABTS assays in descending order were: OME 70 [ OME 30 [ OMW. The antioxidant capacity of the OME 70 was attributed to its higher total phenolic content, as it has been reported that antioxidant activity is directly proportional to total phenolic content (Son et al, 2014). Therefore, the OME 70 was deemed optimal for the extraction of phenolic compounds and was used to evaluate the inhibitory effect of O. malacophyllus on ROS production and adipocyte differentiation in 3T3-L1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this review provide rationale for the use of Opuntia spp. products in applications such as incorporation into functional foods or nutraceuticals, given the additional substantial bioactive contents [18,19,20,21,22,23,24,25,26,27,28,29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The fruit of the cacti is also referred to as the ‘cactus fruit’ or ‘Indian fig’ and also as the PP [6,7] is predominantly known for relatively high levels of macro- and micronutrients including fiber, mineral composition, numerous amino acids; and significant lipid and phytosterol content [13,14,15,16,17]. In addition, there are a number of different bioactive compounds found in PP such as polyphenols [18,19], flavonols [19,20,21] and betalains [18,22,23], as well as considerably strong antioxidant characteristics [17,18,20,21,24,25,26,27,28,29,30,31]. The PP fruit is commonly consumed fresh, although it can be formulated into several different including dried fruits, tea’s, jams, drinks, tinctures and dietary supplements [6,32,33].…”
Section: Introductionmentioning
confidence: 99%